Studi Kasus Simulasi Konfigurasi Jaringan Scada Antara Gedung A dan Gedung B Menggunakan Aplikasi Cisco Packet Tracer - Intan Puspitasari; Muhamad Ryan Agustin; Nuga Pratama; Didik Aribowo (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this article aims to analyze technological developments in the industrial sector. SCADA requires a communication protocol. To increase efficiency in the industrial world, the SCADA system has been widely used in various industrial fields, such as manufacturing, power generation, oil and gas, telecommunications and transportation. Control over the arrangement of an electric power distribution network can be effective and efficient and will be equipped with a SCADA system. Control of the electric power network based on the SCADA system is really necessary considering that the growth of electric power is very high and adds to the increasing complexity of the electric power network system. The SCADA system ((Supervisory Control And Data Acquisition) itself is a system created for data retrieval, storage, analysis and also for controlling a plant/system that has been used remotely.